CRISPR/Cas9-mediated genome engineering: an adeno-associated viral (AAV) vector toolbox - Senís Herrero, Elena; Fatouros, Chronis; Große, Stefanie; Wiedtke, Ellen; Niopek, Dominik; Müller, Ann-Kristin; Börner, Kathleen; Grimm, Dirk (Biotechnology journal, 2014)
Its remarkable ease and efficiency make the CRISPR (clustered regularly interspaced short palindromic repeats) DNA editing machinery highly attractive as a new tool for experimental gene annotation and therapeutic genome engineering in eukaryotes. Here, we report a versatile set of plasmids and vectors derived from adeno-associated virus (AAV) that allow robust and specific delivery of the two essential CRISPR components - Cas9 and chimeric g(uide)RNA - either alone or in combination. All our constructs share a modular design that enables simple and stringent guide RNA (gRNA) cloning as well as rapid exchange of promoters driving Cas9 or gRNA. Packaging into potent synthetic AAV capsids permits CRISPR delivery even into hard-to-transfect targets, as shown for human T-cells. Moreover, we demonstrate the feasibility to direct Cas9 expression to or away from hepatocytes, using a liver-specific promoter or a hepatic miRNA binding site, respectively. We also report a streamlined and economical protocol for detection of CRISPR-induced mutations in less than 3 h. Finally, we provide original evidence that AAV/CRISPR vectors can be exploited for gene engineering in vivo, as exemplified in the liver of adult mice. Our new tools and protocols should foster the broad application of CRISPR technology in eukaryotic cells and organisms, and accelerate its clinical translation into humans.